Penerapan Model Problem Based Learning Berbantuan Flipbook Dalam Pembelajaran Membaca Pemahaman Teks Iklan Pada Peserta Didik Kelas VIII SMP Negeri 25 Kota Bandung - Reni Noviani; Eggie Nugraha; Adi Rustandi (Badan Penerbit STIEPARI Press, 2023)
This research is motivated by the low ability of students in reading comprehension of advertising texts. The purpose of this research is to test the ability of researchers to plan lessons by applying the flipbook-assisted problem-based learning model in teaching reading comprehension of advertising texts; to describe students' abilities before using the flipbook-assisted problem-based learning model in learning to read comprehension of advertising texts; to describe the ability of students after using the flipbook-assisted problem-based learning model in learning to read comprehension of advertising texts; as well as to describe differences in abilities in learning to read and understand advertising texts among students in the experimental and control classes. The method used in this study is a quasi-experimental method. The results of this study proved that researchers were able to plan, implement, and assess the application of flipbook-assisted problem-based learning models in teaching reading comprehension of advertising texts. This is evident from the acquisition of a score of 38 with an average of 3.8 for the experimental class, while for the control class it was 40 with an average of 4. Before using the flipbook-assisted problem-based learning model, students' ability to read and understand advertising texts was still lacking. Good. This is evident from the results of the pretest score with an average of 67.4. The ability of students after using the flipbook-assisted problem-based learning model in learning to read and understand advertising texts increased. This is evident from the results of the posttest score with an average of 83.4. There is a significant difference in learning outcomes between the experimental and control classes. Based on the results of this study, the researchers concluded that the application of the problem-based learning model was effectively used in teaching reading comprehension of flipbook-assisted advertising texts.